ANALISIS YURIDIS TERHADAP PERTANGGUNG JAWABAN PIDANA TINDAK PIDANA PENCURIAN INFORMASI KARTU KREDIT YANG MERUGIKAN NASABAH MELALUI DUNIA MAYA: STUDI PUTUSAN NOMOR 240/PID.SUS/2021/PN.DPS - Andreas Lingga, Masdo; Trisna, Wessy; Lisa Andriati, Syarifah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Credit card hacking (carding) constitutes a form of cybercrime in which offenders unlawfully access and use another person’s credit card for payment transactions without the owner’s consent or knowledge. This study aims to examine and analyze: (1) the legal framework governing the theft of credit card information that causes financial losses to customers through cyberspace; (2) the scope of criminal liability for such offenses; and (3) judicial considerations in Decision Number 240/Pid.Sus/2021/PN.Dps. The research focuses on relevant provisions in Indonesian law, specifically Article 30 paragraph (1) of Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 on Electronic Information and Transactions (ITE), which prohibits unauthorized access to another person’s computer or electronic system. In conjunction with Article 46 paragraph (1) of the ITE Law and Article 55 of the Criminal Code, these regulations form the legal basis for prosecuting carding offenses. Decision Number 240/Pid.Sus/2021/PN.Dps reflects the application of these provisions, where the court imposed penalties on perpetrators consistent with statutory mandates. This research underscores the significance of robust legal enforcement to address the evolving challenges of cybercrime and to safeguard public trust in electronic transactions.